A philosophical analysis of modern ideologies with a focus on transgenderism - Moris, Megawati (2023)
The aim of this research is to investigate on the ideology of transgenderism and analyse its root causes and factors for its increasing popularity as a life stance and behavioural choice during present time. This study will undertake a philosophical analysis of transgenderism from both modern Western and Islamic perspectives since there are fundamental differences between the two perspectives. Hence, this study will take on a critique of the ideology based on the Islamic perspective since Islam is radically opposed to it as a worldview and life stance. The study will examine the consequences of this ideology to society and larger humanity if left to practice and perpetuate as a life stance. Finally, it attempts to find solutions to this problem in terms of clarifying the ideology from the aspects of thought and behavioural action for both individual and society.